Learning through urban labour pools: Collected worker experiences and innovation in services. (November 2019) - Herstad, Sverre J; Solheim, Marte CW; Engen, Marit
Knowledge-intensive services firms depend on the skills and networks of employees and tend to cluster in large-city regions. This raises the fundamental question of whether knowledge-intensive services firms 'learn through urban labour pools' in manners that have implications for innovation. To address it, a distinction is in this paper made between 'related variety' and 'unrelated variety' of work-life experiences collected by employees and combined in firms. The empirical analysis uses innovation survey and register data to demonstrate that higher levels of unrelated variety among staff in urban knowledge-intensive services firms inspire innovation activity and increase the probability of innovation success. Outside cities, where knowledge-intensive services firms on average have more specialized knowledge bases, innovation responds negatively to unrelated variety and positively to related variety. As a result, the sign, size and significance of urban–rural dividing lines in innovation propensities depend on whether firms have cultivated the skill profiles that are most conducive to innovation in their locations. Constraints faced specifically by knowledge-intensive services firms outside cities in this respect are identified and implications for policy drawn.